Munich [large type] - Harris, Robert, 1957- (Random House Large Print, 2017)
A spy thriller set against a backdrop of the fateful Munich Conference of 1938 follows the experiences of a rising star in the British diplomatic service who is on a disastrous collision course with an Oxford friend, a secret member of the anti-Hitler resistance.